PENGARUH KEMAMPUAN SUMBEDAYA MANUSIA TERHADAP KEPUASAN KONSUMEN - Agus Rahmanto; Dwi Rachmadani (Program Studi Ilmu Komunikasi, 2022)
The purpose of this study is to determine whether there is an influence between the ability of human resources on consumer satisfaction at PT. One Bintang Jaya Surabaya. The sample in this study were consumers of PT. Satu Bintang Jaya in January-March 2020 which makes a minimum purchase transaction of Rp. 5,000,000, totaling 40 respondents. This research method is a quantitative method. The results of the f and t test indicate that the ability of human resources affects consumer satisfaction at PT. Satu Bintang Jaya Surabaya. In the coefficient of determination test, the adjuster square value is 55.9%, meaning that the ability of human resources to meet consumer satisfaction is 55.9%. And the remaining 44.1% are other factors. Overall consumer responses to the capabilities of human resources at PT. Satu Bintang Jaya is good.